2022
DOI: 10.34172/jech.2022.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Self-medication in Women of Reproductive Age Based on a Health Belief Model: A Quasi-experimental Study

Abstract: Background: Women of reproductive age have important responsibilities such as pregnancy, breastfeeding, and children raising. This study aimed at surveying the effect of educational interventions, based on the health belief model (HBM), in the prevention of self-medication (SM) in women of reproductive age. Methods: This quasi-experimental study was performed on women of reproductive age in Jahrom in 2019 (January-September). Simple multi-stage random sampling was used to select the participants, and the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…In the present study, findings revealed that the women performance in terms of arbitrary use of medication has been decreased. The similar results were also shown in the studies done by Shamsi, (24) and Hosseini (32) and Izadirad (33) by a reduction in selfmedication. The results of the present study showed that the most drugs arbitrarily used by women before the educational self-medication were painrelievers, antibiotics and cold tablets.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, findings revealed that the women performance in terms of arbitrary use of medication has been decreased. The similar results were also shown in the studies done by Shamsi, (24) and Hosseini (32) and Izadirad (33) by a reduction in selfmedication. The results of the present study showed that the most drugs arbitrarily used by women before the educational self-medication were painrelievers, antibiotics and cold tablets.…”
Section: Discussionsupporting
confidence: 88%
“…Pendekatan teori HBM perlu digunakan untuk mengukur perilaku dan keyakinan setiap orang tentang penggunaan obat (Apriyani & Hanim, 2019). Health Belief Model (HBM) merupakan salah satu model perubahan perilaku kesehatan yang paling banyak digunakan, sering digunakan untuk mencegah penyakit (Hosseini et al, 2022). HBM mencakup persepsi kerentanan (keyakinan abstrak seseorang mengenai kemungkinan tertular suatu penyakit), persepsi keparahan (keyakinan abstrak seseorang tentang tingkat keparahan cedera yang dapat terjadi pada dirinya akibat tertular suatu penyakit), persepsi manfaat (keyakinan terhadap keuntungan dari metode yang diusulkan untuk mengurangi risiko atau memperburuk penyakit), hambatan yang dirasakan (keyakinan tentang dampak alami dan kerugian yang dirasakan dalam melakukan perilaku baru), isyarat untuk bertindak (mempercepat kekuatan yang membuat seseorang merasa perlu untuk bertindak) dan efikasi diri (kepercayaan diri seseorang terhadap kemampuannya untuk melakukan dan mengikuti suatu perilaku dengan sukses) (Jose et al, 2021).…”
Section: Pendahuluanunclassified
“…The Health Belief Model (HBM) is one of the most widely used models of health behavior change, often used to prevent diseases [ 15 ]. The HBM includes perceived susceptibility (a person’s abstract beliefs regarding the possibility of contracting an illness), perceived severity (a person’s abstract belief about the severity of injury that can occur to him as a result of acquiring a disease), perceived benefits (confidence in the advantages of the proposed methods to reduce the risk or worsening of the disease), perceived barriers (beliefs about the natural and perceived costs of pursuing a new behavior), cues to action (accelerating forces that make a person feel the need to act) and self-efficacy (a person’s confidence in his abilities to perform and follow a behavior successfully) [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%